Geodetic Reference Frame for the Americas - Brunini, Claudio Antonio (2013)
SIRGAS (an acronym of the Spanish term for ‘Geocentric Reference System for the Americas’) is an international organisation under the umbrella of the International Association of Geodesy (IAG) and the Pan-American Institute of Geography and History (PAIGH). Its main objective is the defi nition, realisation and maintenance of a state-of-the-art geodetic reference frame in Latin America and the Caribbean. This reference frame must support both highly demanding scientifi c studies and the development of a Spatial Data Infrastructure for the Americas. More than 50 institutions from 19 countries, including the national mapping agencies of Latin America, are committed to SIRGAS in a voluntary partnership.